2018
DOI: 10.1111/gtc.12584
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein disturbs the morphological plasticity and motility of breast adenocarcinoma cells depending on the tumor microenvironment

Abstract: During tumor invasion, cancer cells change their morphology and mode of migration based on communication with the surrounding environment. Numerous studies have indicated that paracrine interactions from non-neoplastic cells impact the migratory and invasive properties of cancer cells. Thus, these interactions are potential targets for anticancer therapies. In this study, we showed that the flavones member baicalein suppresses the motility of breast cancer cells that is promoted by paracrine interactions. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…We found that TAIII suppressed morphological plasticity and migration of breast adenocarcinoma cells induced by conditioned medium from mammary epithelial cells. The activity of conditioned medium from mammary epithelial cells is mainly mediated by secreted laminin-332 [26]. Laminins are a component in the basement membrane of mammary ducts and secreted from myoepithelial cells [7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that TAIII suppressed morphological plasticity and migration of breast adenocarcinoma cells induced by conditioned medium from mammary epithelial cells. The activity of conditioned medium from mammary epithelial cells is mainly mediated by secreted laminin-332 [26]. Laminins are a component in the basement membrane of mammary ducts and secreted from myoepithelial cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…The spatiotemporal regulation of cell surface integrins through tra cking systems gives impact to their functions in the context of cell migration [46][47][48][49][50]. Furthermore, a ligand of integrin heterodimers, laminin-332, plays important roles in the regulation of morphological plasticity and cell migration of MDA-MB-231 cells [26]. Collectively, our results lead us to propose that the activity of TAIII to block internalisation of integrin b1 should contribute, in part, to its inhibitory effect on cell migration through negative regulation of lamellipodia formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations